Long memory and FIGARCH models for daily and high frequency commodity prices - Richard T. Baillie; Young-Wook Han; Robert J. Myers; Jeongseok Song (Queen Mary University of London, Department of Economics, 2007)
Daily futures returns on six important commodities are found to be well described as FIGARCH fractionally integrated volatility processes, with small departures from the martingale in mean property. The paper also analyzes several years of high frequency intra day commodity futures returns and finds very similar long memory in volatility features at this higher frequency level. Semi parametric Local Whittle estimation of the long memory parameter supports the conclusions. Estimating the long memory parameter across many different data sampling frequencies provides consistent estimates of the long memory parameter, suggesting that the series are self-similar. The results have important implications for future empirical work using commodity price and returns data.
Keywords: C4; C22; 330; Commodity returns; Futures markets; Long memory; FIGARCH; Rohstoff-Futures; Volatilit\~AƒÂt; ARCH-Modell; Kapitalertrag